Regioselective Hydroamination Using a Directed Nucleopalladation/Protodepalladation Strategy - Gurak, John A., Jr; Engle, Keary M. (Synlett, 2017)
Alkene hydroamination is an attractive approach for converting alkenes into structurally complex amine products. Several different strategies have been pursued over the past few decades to achieve this historically challenging reaction. One of the key issues associated with this transformation is control of regioselectivity, which is particularly difficult for internal non-conjugated alkenes. Our group has recently found success using a removable bidentate auxiliary to control regioselectivity and stabilize the key nucleopalladated intermediate in a palladium(II)-catalyzed alkene hydroamination with N–H nucleophiles. This article describes the historical context for this work, the underlying conceptual logic, our results to date, and the future outlook.
Keywords: palladium; hydroamination; hydrofunctionalization; nucleopalladation; aza-heterocycles; directing groups